DEVELOP LITERACY SKILLS THROUGH PROBLEM BASED LEARNING BY USING GOOGLE JAMBOARD APPLICATION AT SD GAGASCERIA, BANDUNG - Yais Gumbira Buanawaty (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2021)
Literacy skills do not only develop reading and writing skills. Literacy skills include the ability to interpret, collaborate, solve problems, self-reflect, and communicate. One way to develop this is to use the Problem Based Learning method. Managing learning activities with this method is a challenge, especially during this pandemic. With these challenges, the first and third grade teachers at SD GagasCeria carried out lesson study activities. The purpose of this lesson study is to see how the Problem Based Learning method using the Google Jamboard application can develop students' literacy skills. The subjects of this lesson study are third grade students of SD GagasCeria. We use the stages of lesson study activities, namely Plan-Do-See. One teacher becomes a model teacher and another teacher becomes an observer. They observe learning activities through learning video recordings which are then made in the form of learning transcript analysis. The results of the implementation of this lesson study were analyzed using a qualitative descriptive method. From the results of the analysis, it was found that students' literacy skills could be developed. This can be seen from the results of students' thoughts contained in the Google Jamboard and learning transcripts, showing the level of depth of thinking and understanding of students towards texts, images, and situations at hand. The use of the Google Jamboard application can facilitate students to interact with each other which also helps develop literacy skills.Keywords: Lesson study, literacy, problem based learning, Google Jamboard application.